Sequential administration of doxorubicin and paclitaxel followed by cyclophosphamide, methotrexate and 5-fluorouracil combination (CMF) in women with metastatic breast cancer - Papadimitriou, C.A.; Dimopoulos, M.A.; Ampela, C.; Louvrou-Fertaki, A.; Anagnostopoulos, A.; Athanassiades, P.; Stamatelopoulos, S.; Keramopoulos, A. (Oncology, 1998)
Although the combination of paclitaxel with doxorubicin has yielded high response rates in metastatic breast cancer, severe cardiotoxic events have been reported in several patients. The rationale for our study was to evaluate the activity of paclitaxel/doxorubicin combination in patients with this disease but to avoid excessive cardiotoxicity. Therefore, we administered 4 cycles of doxorubicin/paclitaxel followed by 6 cycles of standard cyclophosphamide, methotrexate and 5-fluorouracil (CMF) regimen. Study medication consisted of doxorubicin 60 mg/m2 as a 15-min intravenous infusion followed by paclitaxel 175 mg/m2 as a 3-hour infusion. CMF regimen consisted of cyclophosphamide 600 mg/m2 as 1-hour intravenous infusion followed by methotrexate 40 mg/m2 and 5-fluorouracil 600 mg/m2 bolus injection. The main toxicity of doxorubicin/paclitaxel treatment phase was neutropenia (WHO grade 3/4, 58%), but we observed only one cardiac adverse event. Toxicities of the CMF treatment phase were not significant. Of 24 patients evaluable for response, 2 (8%) had complete responses and 11 (46%) achieved partial response. Ten additional patients (42%) had stable disease. The median time to progression was 12 months and the median overall survival was 18.5 months. The sequential administration of doxorubicin and paclitaxel followed by CMF appeared active and well tolerated in patients with metastatic breast cancer.
Keywords: CMF combination; Doxorubicin; Metastatic breast cancer; Paclitaxel; Sequential chemotherapy